2021
DOI: 10.1002/prp2.817
|View full text |Cite
|
Sign up to set email alerts
|

Kidney damage from nonsteroidal anti‐inflammatory drugs—Myth or truth? Review of selected literature

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 50 publications
0
20
0
6
Order By: Relevance
“…The inhibition of cyclooxygenases, such as COX-1 and COX2, by NSAIDs also results in high blood pressure and sodium retention. Moreover, TIN can be caused by glomerular basement membrane damage, reduction in pore size, and podocyte density due to the use of NSAIDs [ 29 ]. A meta-analysis found that cyclooxygenase-2 (COX-2) inhibitors and traditional NSAIDs, except naproxen, increased the risk of serious CV events and death [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…The inhibition of cyclooxygenases, such as COX-1 and COX2, by NSAIDs also results in high blood pressure and sodium retention. Moreover, TIN can be caused by glomerular basement membrane damage, reduction in pore size, and podocyte density due to the use of NSAIDs [ 29 ]. A meta-analysis found that cyclooxygenase-2 (COX-2) inhibitors and traditional NSAIDs, except naproxen, increased the risk of serious CV events and death [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Other effects of COX inhibition that influence the cardiovascular system include blood pressure regulation and kidney function. COX inhibitors may induce acute kidney injury, tubulo‐interstitial nephritis, and chronic kidney disease [20]. They prevent the synthesis of PGE 2 and PGI 2 , which increase renal blood flow and glomerular filtration under conditions with decreased circulating volume and decreased renal perfusion [21].…”
Section: (Patho)physiology Of Coxs and Arachidonic Acid Metabolitesmentioning
confidence: 99%
“…The risk is most pronounced in the elderly, those concurrently taking ACE inhibitors or angiotensin-II receptor blockers, and/or diuretics. Individuals with renal dysfunction should use NSAIDs only with great caution under close clinical supervision, if at all [ 22 ].…”
Section: Reviewmentioning
confidence: 99%